EVALUATION OF CLINICAL EFFICACY AND TOLERANCE OF KHASCEEZE –SF COUGH SYRUP (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Fifty patients of either sex aged 15 - 65 years entered the study to test the efficacy and tolerability of a herbal preparation known as Khasceeze-SF Cough Syrup. They were studied for cough and related symptoms such as sore throat, sneezing, breathlessness and fever. Substantial improvement, i.e., excellent to good response, in relief of cough and other symptoms was noted over 84% out of 50 patients and fair response in 11.64%. Only 4.10% patients showed poor relief in symptoms hence suggested Khasceeze-SF Cough Syrup facilitated a healing touch to the diseased bronchial tree and helps alleviate the cough of any aetiology. No drowsiness, irritability, or dryness in mouth was seen with Khasceeze-SF Cough Syrup.